The dietary phytochemicals carnosic acid and sulforaphane regulate inflammatory markers in ulcerative colitis patient-derived colonoids - Rivera Rodríguez, Rocío; Sæterstad, Siri; Chattergoon Ali, Ann-Therese; Selvik, Linn-Karina M.; Bakke, Ingunn; Bruland, Torunn; Johnson, Jeremy J. (Frontiers in Pharmacology, 2025)
IntroductionThe inflammatory bowel disease (IBD) ulcerative colitis (UC) is characterized by continuous inflammation of the colon with erosion and ulcers. Diagnosis typically occurs in patients between their late teens and mid-30s with no cure. Available therapeutics are efficient at controlling symptoms however, they have many serious adverse effects. Thus, additional therapies with limited adverse effects are needed to complement these drugs. In this study, we evaluated the anti-inflammatory potential of carnosic acid (CA), the most abundant diterpene in rosemary (Salvia rosmarinus) and sulforaphane (SFN), an isothiocyanate found in cruciferous vegetables.MethodsWe used colonic epithelial organoids (colonoids) derived from non-IBD and UC patients as a physiologically relevant testing platform for both phytochemicals. These patient-derived colonoids are a representative model that recapitulates the parent epithelial tissue including its cellular composition and 3D structure. Moreover, we cultured the colonoids at 2% O2 to better approximate the low oxygen level (physioxia) observed in the colon crypts. To assess the effects of CA and SFN in the nuclear factor erythroid 2-related factor 2 (NRF2) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathways, we studied modulation of inflammatory cytokines through a 40-plex chemokine assay and ELISA, as well as gene and protein expression of target genes with qPCR and western blot, respectively.ResultsThrough these techniques, we observed that CA and SFN decreased inflammatory markers and promoted NRF2 activity in patient-derived colonoids. Additionally, SFN and CA modulated the expression and secretion of the NF-κB promoted antibacterial peptide neutrophil gelatinase-associated lipocalin which is highly expressed in the inflamed colonic epithelium and has been suggested as a biomarker for active UC.DiscussionTogether, the results validated the use of colonoids as a pharmacological testing platform for phytochemicals, and that CA and SFN promote NRF2 activation and decrease inflammation in a human physiologically relevant UC model.